Design of Dissolvable Milk Containers for Convenient Handling. Issue 7 (12th May 2017) - Wellner, Martha; Ulrich, Joachim
Abstract: A dissolvable capsule containing liquid milk is developed as an innovative and unique alternative to avoid plastic jars and therewith an unclean handling. This kind of sustainable product would contribute to waste reduction. As a first step, the properties of the final product are defined and set as basic claims. The second step includes the design of a process based on crystallization to form a crystalline layer encasing a certain amount of milk. Case studies of two substances are introduced. Both sucrose and erythritol were confirmed as examples for suitable substances for the encapsulation of milk: on the one hand sucrose to create products with a high level of sweetness, on the other hand erythritol to create medium sweet milk capsules. The choice of both coating substances and filling materials requires different techniques of production and, therefore, an adapted optimization process. Abstract : An alternative packaging for milk or condensed milk as an innovative and unique alternative to common plastic jars is introduced. A method is developed to encapsulate milk or condensed milk by means of crystallization. Successful encapsulation is demonstrated creating capsules with a hard and stable crust. Sucrose and erythritol are used to form a crystalline layer.